1997
DOI: 10.1210/jcem.82.6.3988
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement in Older Hypogonadal Men: A 12-Month Randomized Controlled Trial

Abstract: A decline in testicular function is recognized as a common occurrence in older men. However data are sparse regarding the effects of hypogonadism on age-associated physical and cognitive declines. This study was undertaken to examine the year-long effects of testosterone administration in this patient population.Fifteen hypogonadal men (mean age 68 Ϯ 6 yr) were randomly assigned to receive a placebo, and 17 hypogonadal men (mean age 65 Ϯ 7 yr) were randomly assigned to receive testosterone. Hypogonadism was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
437
4
19

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 670 publications
(477 citation statements)
references
References 46 publications
17
437
4
19
Order By: Relevance
“…In men, however, decreased testosterone causes an increase in leptin levels despite a decline in total fat mass (4). Testosterone replacement results in leptin levels decreasing (28). This suggests that elevated leptin levels play a role in the greater anorexia developed by males with aging.…”
Section: Anorexia Of Aging: An Example Of Hormonal Dysregulationmentioning
confidence: 97%
See 1 more Smart Citation
“…In men, however, decreased testosterone causes an increase in leptin levels despite a decline in total fat mass (4). Testosterone replacement results in leptin levels decreasing (28). This suggests that elevated leptin levels play a role in the greater anorexia developed by males with aging.…”
Section: Anorexia Of Aging: An Example Of Hormonal Dysregulationmentioning
confidence: 97%
“…Table 4 summarizes a number of studies demonstrating positive effects of testosterone replacement in men, similar to those seen with estrogen in women (25). In humans, testosterone increases muscle mass (26), muscle strength (27)(28)(29), bone mineral density (29,30), hemoglobin (28), and visuospatial cognitive function (31). Studies in the SAMP8 mouse, an animal model of Alzheimer disease (32), suggest that testosterone may play a role in the decline in memory and the overproduction of amyloid-6 protein seen in this species (14).…”
Section: The Hormonal Fountain Of Youthmentioning
confidence: 99%
“…In most of these studies, the body weight change did not differ significantly. Testosterone therapy was associated with a greater improvement in grip strength than placebo [37,74,75]. A recent double-blind placebo-controlled study showed benefits of testosterone administration on skeletal muscle performance in elderly men with chronic heart failure [76], and another one found positive effects on the prevention of loss of muscle strength of the lower limbs [77].…”
Section: Muscle Mass and Strengthmentioning
confidence: 99%
“…Hypertriglyceridemia blocks the ability of leptin to cross the blood–brain barrier 32. Male hypogonadism leads to an increase in leptin 33. The effects of ageing on ghrelin are controversial 34.…”
mentioning
confidence: 99%